Website Design and Development to Help Create and Develop a Business to Increase the Number of MSMEs - Yogi Prasetyo; Btari Mariska Purwaamijaya; Syti Sarah Maesaroh (Institute of Computer Science (IOCS), 2022)
The Covid-19 pandemic is now having quite serious consequences for the sustainability of the economy in Indonesia, this is because the government has established a policy of limiting community social activities where this policy is used to reduce the spread of Covid-19. As a result of this policy, economic activity barely runs at all. Because of this, the total number of MSMEs in Indonesia inevitably experienced a drastic decline and increased the number of unemployed. requires a treatment that is in line with current technological developments. One strategy to increase the number of MSMEs and reduce unemployment can be done by developing a website-based application that will be named